Perubahan Sosial dan Respon Masyarakat Lokal Akibat Perkembangan Pariwisata di Desa Sapit, Lombok Timur - Amrina, Lisa; Karyadi, Lalu Wiresapta; Hamdi, Saipul (Religion, Culture, and State Journal, 2021)
Sapit village is an affluent area in terms of natural, cultural, and artistic resources. This wealth is used to develop tourism, and various tourist objects have been developed to attract local and foreign tourists. Tourism development is one form of policy in improving the community’s economy, but the impact of tourism will always appear in terms of community social life, especially in the Sapit Village community, East Lombok Regency. Social changes cannot be avoided due to interactions between local communities and tourists. Therefore, this study aims to uncover and explain social changes and local community responses due to tourism developments. This research applied a qualitative method with a descriptive approach. Data were taken through observation, interviews, and documentation. Data were analyzed using Miles and Huberman’s interactive analysis model. The results of this study indicate that the people of Sapit Village experienced changes in socio-economic aspects and socio-cultural aspects. Changes in socio-economic aspects include four change indicators, namely in production, distribution, consumption, and institutional activities. Meanwhile, changes in socio-cultural aspects include three indicators: changes in the essence and existence of social capital, values â€‹â€‹and norms, and cultural institutions. The local community’s response to tourism development is divided into two, namely those who agree because they feel the economic or material impact directly due to tourism and the response of local communities who do not agree because of the fiqh studies they have and logically understand the negative impact of tourism development.